1985
DOI: 10.1152/ajpheart.1985.248.5.h637
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase enhances recovery following myocardial ischemia

Abstract: Oxygen-derived free radicals, specifically superoxide (O-2) and the hydroxyl radical (OH.), have been implicated as possible mediators in the development of myocardial damage induced by ischemia and reflow. The purpose of this study was to examine the ability of superoxide dismutase (SOD), a O-2 scavenging enzyme, to protect the heart against functional and structural alterations due to ischemia and reflow. An isolated perfused rabbit interventricular septal preparation was used for these experiments. Septa we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
1
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 0 publications
1
34
1
1
Order By: Relevance
“…The evidence is based on the observed protective effect of superoxide dismutase [4] and/ or catalase 11, 2, 51 during ischemia and reperfusion. There are also reports that inhibition of the enzyme xanthine oxidase (a potential source of 0;) also affords protection to the ischemic myocardium [2, 31.…”
mentioning
confidence: 99%
“…The evidence is based on the observed protective effect of superoxide dismutase [4] and/ or catalase 11, 2, 51 during ischemia and reperfusion. There are also reports that inhibition of the enzyme xanthine oxidase (a potential source of 0;) also affords protection to the ischemic myocardium [2, 31.…”
mentioning
confidence: 99%
“…CuZn-SOD has been reported to protect various organs from the damage caused by oxygen radicals (7,18,42). The uterine cervix, especially the region covered with stratified squamous epithelium, is at risk to high atmospheric oxygen tension.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that oxygen-derived free radicals may contribute to the myocardial injury associated with ischemia and reperfusion (1)(2)(3)(4)(5). Recently, using electron spin resonance (ESR) spectroscopy (6-15) and enhanced chemiluminescence (16), direct evidence of increased oxy gen-derived free radical production during reperfusion has been obtained.…”
mentioning
confidence: 99%